Analisis Kesalahan Berbahasa Pada Media Spanduk di Lingkungan Masyarakat (Kajian Morfologi) - Rizki, Nabilha Legita; Syahfitri, Ramadania; Sahfitri, Yulia; Surip, M (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The correct use of Indonesian must be in accordance with applicable rules, such as spelling, word formation, sentence construction, paragraph arrangement, and reasoning arrangement. Compliance with these rules determines the correctness of language use. However, observing the billboards around shows that many of them do not pay attention to the use of standard language. People often write words or sentences that can be understood by everyone without paying attention to Enhanced Spelling (EYD). Although the non-standardity of billboards is sometimes overlooked by readers, as native speakers of Indonesian, people have a responsibility to preserve linguistic rules. Therefore, this research analyzes the writing of information on billboards, banners and signs in the community to evaluate the extent of compliance with Indonesian language rules.